Natural rubber latex coated with calcium phosphate for biomedical application - Borges, Felipe Azevedo [UNESP]; Almeida Filho, Edson de [UNESP]; Miranda, Matheus Carlos Romeiro [UNESP]; Santos, Márcio Luiz dos [UNESP]; Herculano, Rondinelli Donizetti [UNESP]; Guastaldi, Antônio Carlos [UNESP] (Informa UK Limited, 2014)
Natural rubber latex (NRL) is a flexible biomembrane that possesses angiogenic properties and has recently been used for guided bone regeneration, enhancing healing without fibrous tissue, allergies or rejection. Calcium phosphate (Ca/P) ceramics have chemical, biological, and mechanical properties similar to mineral phase of bone, and ability to bond to the host tissue, although it can disperse from where it is applied. Therefore, to create a composite that could enhance the properties of both materials, NRL biomembranes were coated with Ca/P. NRL biomembranes were soaked in 1.5 times concentrated SBF solution for seven days, avoiding the use of high temperatures. SEM showed that Ca/P has been coated in NRL biomembrane, XRD showed low crystallinity and FTIR showed that is the carbonated type B. Furthermore, hemolysis of erythrocytes, quantified spectrophotometrically using materials (Ca/P, NRL, and NRL + Ca/P) showed no hemolytic effects up to 0.125 mg/mL (compounds and mixtures), indicating no detectable disturbance of the red blood cell membranes. The results show that the biomimetic is an appropriate method to coat NRL with Ca/P without using high temperatures, aiming a new biomembrane to improve guided bone regeneration.
Keywords: Calcium phosphate (Ca/P); Simulated body fluid; Natural rubber latex; Biomembrane; Guided bone regeneration